If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(3x+7)+5=4(x+8)+41
We move all terms to the left:
5(3x+7)+5-(4(x+8)+41)=0
We multiply parentheses
15x-(4(x+8)+41)+35+5=0
We calculate terms in parentheses: -(4(x+8)+41), so:We add all the numbers together, and all the variables
4(x+8)+41
We multiply parentheses
4x+32+41
We add all the numbers together, and all the variables
4x+73
Back to the equation:
-(4x+73)
15x-(4x+73)+40=0
We get rid of parentheses
15x-4x-73+40=0
We add all the numbers together, and all the variables
11x-33=0
We move all terms containing x to the left, all other terms to the right
11x=33
x=33/11
x=3
| x=2.4-18 | | 3x-50=0.2x+20 | | -4p-10=-6p+2 | | 8x–20=28 | | x+2×+3x+4x+5x=30 | | 2.4x+7=19 | | F(x)=4/3(-5)-5 | | -15=x/3-5 | | −8=5p−13p | | 68+121+103+85+x=540 | | X+.2X=y | | 4x+5-3x-7=2x+5(-3x+6-8) | | 5-3g+7g=3+5g | | -4n=-4(8n+6)-4 | | 4x+10=-6x-70 | | 3x-50=1/5x+20 | | -18x-3x=105 | | 5r=8.6 | | 2x+6=-1-8 | | -1/2e=9 | | F(-5)=4/3x-5 | | 1.8j-3.47=-6.02+3.9j-2.4j | | 8x−16=4x−56 | | 10x-32=88 | | 3x+1+2x+2=48 | | 9(3x+5)−18=5(2x+6)+31 | | 6x+7+2x-11=180 | | 5x-2x+7=21 | | 3x+2/7=5x-4 | | 116=6x-2 | | 3^(6x+5)=5^(2x-1) | | q - 12 = 1 |